(untitled) (Physical Education, Health and Social Sciences, 2025)
This study highlights the complexities of overlapping life-threatening conditions—acute respiratory distress syndrome (ARDS), Guillain-Barré syndrome (GBS), and falciparum malaria—that must be diagnosed and managed in resource-poor settings. A 16-year old young girl presented with 7day history of fever, diarrhea, lower limb weakness, and rectal bleeding. Initial screening confirmed Plasmodium falciparum malaria. She subsequently developed ARDS and GBS, evidenced by albuminocytologic dissociation of cerebrospinal fluid. In spite of mechanical ventilation, intravenous artesunate, and corticosteroids, the patient deteriorated and died on day 8. The case points to the necessity of early diagnosis of GBS in malaria-endemic regions and advocates for multidisciplinary approaches in resource-constrained environments.